Determination of the Corrosion Rate of Steel Bars in Concrete Based on the Porosity of Interfacial Zone - Zheng, Xuan; Yang, Sanqiang; Sun, Shuang (Frontiers in Materials, 2020)
In the present paper, a simple model to predict the corrosion rate of steel bars in concrete is developed, considering the influence of the porosity of steel-concrete interfacial zone. Firstly, a model for the porosity of the interfacial zone is developed basing on the water-cement ratio gradient in the interfacial zone. Then the relationship between the porosity of the interfacial zone and the corrosion parameters of the steel bar in concrete is discussed, the anode-cathode ratio for the electrochemical corrosion process, the chloride threshold value and the resistivity of concrete are determined by the porosity of steel-concrete interfacial zone. The corrosion rate of steel bars, which is taken as the corrosion current density, is calculated by considering the cathodic concentration polarization of oxygen diffusion and resistance polarization of concrete, basing on the determined parameters above. Finally, the applicability and efficiency of the corrosion rate prediction model is verified by experiments.